256 Spectrophotometric Properties of 31 Different Commercially Available Blue Blocking Glasses Under Electric Room Lighting. (3rd May 2021) - Rupple, Destiny; Mason, Brooke; Tubbs, Andrew; Fernandez, Fabian-Xosé; Grandner, Michael
Abstract: Introduction: Blue blocking glasses are often marketed to promote relaxation, sleep, and circadian health by attenuating melatonin-suppressing light exposure. But these glasses represent a wide range of tint and other lens properties. Further, the utility of these glasses under ecologically valid indoor conditions (where light is typically generated from overhead broadspectrum fluorescent lamps) is still unclear, especially across various products. Methods: A calibrated spectroradiometer (Ocean Insight), cosine corrector, optic fiber, and software package were used to measure the absolute irradiance (uW/cm^2/nm) emitted from overhead fluorescent lighting in a closeted dark room. Thirty-one commercially available blue blockers were individually placed between the cosine corrector and the luminaire, at a standardized distance and angle, where intensity was measured and analyzed. Each lens was evaluated individually relative to the light source under identical conditions. Then, lenses were collapsed by type into the following groups: red-tinted lenses (RTL), orange-tinted lenses (OTL), orange-tinted lenses with blue reflectivity (OBL), brown-tinted lenses (BTL), yellow-tinted lenses (YTL), and clear reflective blue lenses (RBL). Results: There was significant variation in light-blocking across lens types (one-way ANOVA, p < 0.0001). On average, RTL and BTL restricted 59% of the visible light measured from 380-780nm. OTL blocked 47% of the light in this range, while OBL blocked 29%. Both YTL and RBL blocked 14% of the exposure. When narrowing the range of light to 440-530nm (the part of the spectrum most likely to produce a response from melanopsin-expressing retinal ganglion cells), we estimated the following performance: the RTL and OTL blocked close to 100% of the light, OBL blocked 98%, BTL blocked 80%, YTL blocked 33%, and RBL blocked 15%. These differences were statistically significant (one-way ANOVA, p < 0.0001). Individual lenses performed variably within groups, but these differences were small. Conclusion: Focusing on the portion of the visible spectrum most likely to suppress melatonin secretion, RTL and OTL blocked exposure the best, followed by OBL, BTL, YTL, and (lastly) RBL. Support (if any): R01MD011600, R01DA051321